Neurophysiological Correlates of Asymmetries in Vowel Perception: An English-French Cross-Linguistic Event-Related Potential Study - Polka, Linda; Molnar, Monika; Zhao, T. Christina; Masapollo, Matthew (Frontiers in Human Neuroscience, 2021)
Behavioral studies examining vowel perception in infancy indicate that, for many vowel contrasts, the ease of discrimination changes depending on the order of stimulus presentation, regardless of the language from which the contrast is drawn and the ambient language that infants have experienced. By adulthood, linguistic experience has altered vowel perception; analogous asymmetries are observed for non‐native contrasts but are mitigated for native contrasts. Although these directional effects are well documented behaviorally, the brain mechanisms underlying them are poorly understood. In the present study we begin to address this gap. We first review recent behavioral work which shows that vowel perception asymmetries derive from phonetic encoding strategies, rather than general auditory processes. Two existing theoretical models – the Natural Referent Vowel framework and the Native Language Magnet model – are invoked as a means of interpreting these findings. Then we present the results of a neurophysiological study which builds on this prior work. Using event-related brain potentials (ERPs), we first measured and assessed the mismatch negativity response (MMN, a passive neurophysiological index of auditory change detection) in English and French native-speaking adults to synthetic vowels that either spanned two different phonetic categories (/y/ vs. /u/) or fell within the same category (/u/). Stimulus presentation was organized such that each vowel was presented as standard and as deviant in different blocks. The vowels were presented with a long (1,600-ms) inter-stimulus interval to restrict access to short-term memory traces and tap into a “phonetic mode” of processing. MMN analyses revealed weak asymmetry effects regardless of the (i) vowel contrast, (ii) language group, and (iii) MMN time window. Then, we conducted time-frequency analyses of the standard epochs for each vowel. In contrast to the MMN analysis, time-frequency analysis revealed significant differences in brain oscillations in the theta band (4–8 Hz), which have been linked to attention and processing efficiency. Collectively, these findings suggest that early-latency (pre-attentive) mismatch responses may not be a strong neurophysiological correlate of asymmetric behavioral vowel discrimination. Rather, asymmetries may reflect differences in neural processing efficiency for vowels with certain inherent acoustic-phonetic properties, as revealed by theta oscillatory activity.